Taking Flight with Copilot: Early insights and opportunities of AI-powered pair-programming tools - Bird, Christian; Ford, Denae; Zimmermann, Tom; Forsgren, Nicole; Kalliamvakou, Eirini; Lowdermilk, Travis; Gazit, Idan (ACM Queue, 2023)
Over the next five years, AI-powered tools likely will be helping developers in many diverse tasks. For example, such models may be used to improve code review, directing reviewers to parts of a change where review is most needed or even directly providing feedback on changes. Models such as Codex may suggest fixes for defects in code, build failures, or failing tests. These models are able to write tests automatically, helping to improve code quality and downstream reliability of distributed systems. This study of Copilot shows that developers spend more time reviewing code than actually writing code. As AI-powered tools are integrated into more software development tasks, developer roles will shift so that more time is spent assessing suggestions related to the task than doing the task itself.